SPE International Symposium and Exhibition on Formation Damage Control 2004
DOI: 10.2118/86483-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Limits in Hydraulic Fracture Design

Abstract: In a number of previous publications we have introduced the concept of Unified Fracture Design (UFD) with a central theme of maximizing the dimensionless productivity index (JD) following a hydraulic fracture treatment. We have shown that for a given mass of proppant to be injected in a well with an assigned drainage in a reservoir of a given permeability there exists a specific dimensionless fracture conductivity at which the JD becomes maximum. We called this the optimum conductivity. Smaller and larger valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 5 publications
1
25
1
Order By: Relevance
“…One of the clear messages is that the better the proppant the larger the indicated treatment should be and not the opposite as very conservative past practices have suggested. Similar findings have already been shown with a large set of parametric studies presented by Economides et al [2][3] , as well as in a field case study of almost a thousand hydraulic fracture treatments in Western Siberia in which Diyashev and Economides 4 provided a substantial experimental confirmation to the concept.…”
Section: Benchmarking Well Performance With the Unified Fracture Desisupporting
confidence: 83%
See 1 more Smart Citation
“…One of the clear messages is that the better the proppant the larger the indicated treatment should be and not the opposite as very conservative past practices have suggested. Similar findings have already been shown with a large set of parametric studies presented by Economides et al [2][3] , as well as in a field case study of almost a thousand hydraulic fracture treatments in Western Siberia in which Diyashev and Economides 4 provided a substantial experimental confirmation to the concept.…”
Section: Benchmarking Well Performance With the Unified Fracture Desisupporting
confidence: 83%
“…Even more, in some very progressive areas this design approach has been used to "push the limits" of today's practices in hydraulic fracturing. Economides, Demarchos et al [2][3] showed, for example, how relevant the mass of proppant is for the maximization of the productivity index. Diyashev and Economides 4 presented field case studies of almost a thousand hydraulic fracture treatments in Western Siberia, providing a very valuable experimental support for the UFD approach.…”
Section: Introductionmentioning
confidence: 99%
“…The gas specific gravity is 0.65, and all PVT parameters are calculated using PVT correlations (Economides et al, 1994) under average reservoir pressure 6,000 psi and temperature 180°F. The flow rate used for all simulations is 100 MMscf/D.…”
Section: Gas Well Sensitivity Studiesmentioning
confidence: 99%
“…Unrestricted fracturing, long-established for low-permeability reservoirs is not applicable to high-permeability formations where the resulting width would be far less than indicated by rigorous design approaches such as the Unified Fracture Design (UFD) (Economides et al, 2002). Thus, tip screenout (TSO) treatments are necessary, in which the lateral migration of the fracture is arrested followed by inflation of the fracture to the desired/optimum width.…”
Section: Introductionmentioning
confidence: 99%
“…The well performance in a square reservoir depends on the x-direction penetration ratio I x : The penetration ratio and the dimensionless fracture conductivity through the fracture width compete for the same resource, the proppant volume in the fracture. Therefore, the propped volume provides a constraint: .. (4) where N prop has been defined by Economides et al (2002) as the dimensionless proppant number. V p is the volume of the proppant in the pay.…”
Section: Introductionmentioning
confidence: 99%